2019
DOI: 10.3390/plants8080246
|View full text |Cite
|
Sign up to set email alerts
|

An Ethnobotanical Survey of Medicinal Plants Used in Papantla, Veracruz, Mexico

Abstract: An ethnobotanical study was performed to collect information on the use of medicinal plants in Papantla, Veracruz, Mexico. The area has a high number of endemic species, and the social importance of the medicinal plants in the community is essential for public health and the conservation of traditional knowledge. This study identified the medicinal plants currently used, registered traditional knowledge, and documented the patterns of ailments treated in the indigenous communities of Totonacas. A total of 101 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
1
18
0
4
Order By: Relevance
“…For example, Reimers et al . [ 27 ] and Salehi et al . [ 28 ] reported the use of Aloe vera to treat hair problems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Reimers et al . [ 27 ] and Salehi et al . [ 28 ] reported the use of Aloe vera to treat hair problems.…”
Section: Resultsmentioning
confidence: 99%
“…f., Acorus calamus L., Apium graveolens L., and Allium fistulosum L. have been reported in previous ethnobotanical studies. For example, Reimers et al [27] and Salehi et al [28] reported the use of Aloe vera to treat hair problems. Meanwhile, the use of Acorus calamus L. to treat fever has been reported by Rajput et al [29].…”
Section: Plos Onementioning
confidence: 99%
“…North America showed contrasting results. Limited jobs and lack of funding is a considerable limitation ( Barkaoui et al , 2017 ), and hence TBK mainly was under practice in some parts of Mexico ( Saynes-Vásquez et al , 2016 ; Lara Reimers et al , 2019 ). Occasionally, children from privileged families having private insurance in the USA were seen using complementary and alternative medicine (CAM) as a supplement to conventional medicine ( Barnes et al , 2008 ).…”
Section: Urban Ethnopharmacology: Emergence and Present Status Throughout The Globementioning
confidence: 99%
“…It is known by Thai people that the mucilaginous leaves of L. glutinosa are used in combination with kafir lime and flower of butterfly pea for Thai traditional shampoo ( Panyadee et al, 2016 , Wisetkomolmat et al, 2019 ). Gender was also not significantly correlated to knowledge of plant utilisation ( Lara Reimers et al, 2019 ).…”
Section: Discussionmentioning
confidence: 93%